Prevalence and Associated Factors of Self Medication with Prescription Drugs among Saudi Adults - Tannir, Mohamad Al (International Journal of Pharmaceutical & Biological Archive, 2016)
Prevalence and Associated Factors of Self Medication with Prescription Drugs among Saudi Adults